Collecting: a way of exploring the difficulty to leave game world - Guo, Yichen (2015)
Digital games have become a part of daily life for people in recent years. they have the capacity of making game users set playing games as top priority in daily life. In this sense, playing digital games can break the balance between the virtual and the reality and it is possible that some people may get lost in the virtual world. However, this thesis argues that it can be inappropriate just equating excessive play with addiction. By discussing and connecting previous literature reviews on games and addiction, as well as adding three game case studies, this thesis finally finds collecting as a different approach to explore the difficulty to leave game world. Through discussing in-game collecting and book collecting in ancient China, this thesis helps answer how people understand the heavy use on digital games and what is hidden behind choosing to stay in game world.